The importance of measuring ionized calcium in characterizing calcium status and diagnosing primary hyperparathyroidism - Ong, Gregory S Y; Walsh, John P; Stuckey, Bronwyn G A; Brown, Suzanne J; Rossi, Enrico; Ng, Jennifer L; Nguyen, Hieu H; Kent, G Neil; Lim, Ee Mun (The journal of clinical endocrinology and metabolism, 2012)
Serum total calcium (tCa) is routinely measured for diagnosing calcium disorders but may not reflect levels of biologically active ionized calcium (iCa) in disease or detect all cases of primary hyperparathyroidism. We investigated the utility of measuring iCa and tCa for diagnosing primary hyperparathyroidism. This was an observational, retrospective, cross-sectional study. We studied a biochemistry cohort of consecutive ambulatory outpatients with suspected bone or calcium metabolism disorders referred for calcium metabolism biochemistry panels and a surgical cohort of consecutive tertiary hospital patients whose parathyroid specimens were submitted to a single center, and consecutive parathyroidectomy patients of a single surgeon with specimens submitted to a different center. In 5490 biochemistry cohort patients, discordance between iCa and tCa in classifying calcium status occurred in 12.6% of cases overall but was worse in hypercalcemic (whether defined by tCa and/or iCa) cases (49%) and hypocalcemic cases (92%). Reliance on tCa alone would miss 45% with ionized hypercalcemia. In 315 biochemistry cohort cases with PTH-dependent hypercalcemia, 130 (41%) had isolated ionized hypercalcemia at diagnosis. In 143 patients with histologically proven parathyroid disease, 24% had isolated ionized hypercalcemia at diagnosis. These patients were younger (P = 0.022) with milder ionized hypercalcemia and better renal function (both P ≤ 0.001) than patients presenting with concurrently elevated iCa and tCa. In abnormal calcium states, tCa frequently disagrees with iCa in classifying calcium status. Histologically proven parathyroid disease can present with isolated ionized hypercalcemia. Measurement of iCa is required to accurately assess calcium status and improve diagnostic accuracy.